1996
DOI: 10.1021/jo960942f
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of N-Benzyl-1,4-dihydropyridines, Cyclohexenones, and Bicyclo[3.3.1]nonan-3-one Derivatives from 1-Aza-1,3-butadienes

Abstract: Readily available 1-aza-1,3-butadienes (enimines) react with methyl acetoacetate and acetylacetone in the presence of catalytic amounts of lithium iodide to form in high yields unsymmetrically substituted 1,4-dihydropyridines or cyclohexenones. The reaction pathway depends on the structure of the enimine used. This divergence was not observed when the enimines were reacted with dimethyl 1,3-acetonedicarboxylate to provide bicyclo[3.3.1]nonane-3-one derivatives in excellent yields in a remarkably stereoselectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…On the other hand, we observed a good regioselectivity in favor of 4 e (entry 3) arising from a selective C-alkylation at the more accessible C5-position. The expected structure and stereochemistry of 4 e, f were detucted from extensive 1 H and 13 C NMR studies using essentially homonuclear correlations as shown on Figure 6 for compound 4 e. Cycloheptanones 1 g, h also give excellent yields of the corresponding tri-and tetracyclic enol ethers 4 k, l but surprisingly, a significant loss of the trans-selectivity was observed leading to a trans/cis ratio of 17 and 6.5, respectively (entries 8,9).…”
Section: Ketonementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we observed a good regioselectivity in favor of 4 e (entry 3) arising from a selective C-alkylation at the more accessible C5-position. The expected structure and stereochemistry of 4 e, f were detucted from extensive 1 H and 13 C NMR studies using essentially homonuclear correlations as shown on Figure 6 for compound 4 e. Cycloheptanones 1 g, h also give excellent yields of the corresponding tri-and tetracyclic enol ethers 4 k, l but surprisingly, a significant loss of the trans-selectivity was observed leading to a trans/cis ratio of 17 and 6.5, respectively (entries 8,9).…”
Section: Ketonementioning
confidence: 99%
“…[3] However, in spite of the synthetic usefulness of these systems, only few reports deal with the reactivity of readily accessible 1,3-diactivated ketones. [4] In the acyclic version, utilization of commercially available dialkyl 1,3-acetonedicarboxylates has led to interesting transformations by reaction with various dielectrophiles such as 1,3-diacetals, [5] 1,2-dicarbonyls, [6] a-bromomethyl acrylates, [7] 1-aza-1,3-butadienes, [8] a,b-unsaturated aldehydes, [9] bisbromomethyl aromatics, [10, 11a] and other a,w-dihalides. [11b,c] On the other hand, the chemistry of anionic species derived from cyclic 1,3-ketodicarboxylates has found only limited applications.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their biological activities and synthetic point of view few efficient routes have been developed, these are the reaction between α,β-unsaturated imines and β-dicarbonyl compounds in the presence of sodium ethoxide 9 at 150 ℃, Michael reaction followed by cyclization between a β-dicarbonyl compound and α,β-unsaturated imine in the presence of lithium iodide 10 and hetero Diels-Alder reactions of 1-azadienes and allenic esters 11 to generate the N-aryl and C 5 -C 6 -unsubstituted systems. However many of these procedures have one or more disadvantages such as refluxing at high temperature, long reaction times (55-85 h), requiring unusual starting materials, using toxic solvents, forming side products, low yields, and difficulties in workup.…”
Section: Introductionmentioning
confidence: 99%
“…Robinson type annelations) [5,6], and alkylations of enolizable 1,3-cyclohexadiones [7]. Recently, N-tert-butyl-1-aza-1,3-butadienes have been reacted with -diketones to furnish 2-cyclohexenones [8]. One of us has described the synthesis of 2-cyclohexenones via a Michael-Wittig condensation of substituted 2H-pyran-5-carboxylates and the -arsonium ylide of acetoacetate [9] which is based on a similar observation obtained from condensations of conjugated unsaturated carbonyl compounds and the -phosphonium ylide of acetoacetate [10].…”
Section: Introductionmentioning
confidence: 99%